REALIZATION OF HIGH IPF ICE SLURRY FOR DISTRICT COOLING - 이윤표; SANG HOON LEE; 유호선 (대한설비공학회, 2010)
The Production of high IPF (ice packing factor) ice slurry was realized. The ice slurry maker which can efficiently produce ice slurry under ice particles in-flowing condition was revised. We removed the stagnant region at the top of the ice slurry maker, thereby high IPF ice slurry was realized. The IPF controller with 6 mm diameter holes could not control IPF in a pipe. This is because ice particles in ice slurry flow exist homogeneously not only at the upper part but also at the bottom part. We changed the hole size at the surface of the IPF controller by means of fine meshes, which, then, increased the IPF in the pipe by 70% when the mesh size was 80 μm or less.